2014
DOI: 10.1016/j.jrras.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation exposure levels at Alaba e-waste dumpsite in comparison with municipal waste dumpsites in southwest Nigeria

Abstract: a b s t r a c tRadiation exposures at the e-waste dumpsite around Alaba International Market, Lagos and three municipal waste dumpsites located in Ibadan and Ado Ekiti, southwest Nigeria were assessed by gamma ray spectroscopy using a highly shielded Canberra NaI (Tl) detector. Soil samples were collected for analysis at the municipal waste dumpsites for comparison with e-waste dumpsite. Samples were also collected at a location free from waste dumps to serve as control. The mean concentrations of 40 K, 226 Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The impact of e-waste on human health has been devastating. Communities near e-waste recycling sites are prone to health and safety concerns such as inhalation of toxic chemicals and exposure to radiation (Jibiri et al, 2014). A study by Machete (2017) in South Africa confirmed human exposure to toxic metals such as arsenic, mercury, and cadmium whose effect on human health is catastrophic.…”
Section: Human Healthmentioning
confidence: 99%
“…The impact of e-waste on human health has been devastating. Communities near e-waste recycling sites are prone to health and safety concerns such as inhalation of toxic chemicals and exposure to radiation (Jibiri et al, 2014). A study by Machete (2017) in South Africa confirmed human exposure to toxic metals such as arsenic, mercury, and cadmium whose effect on human health is catastrophic.…”
Section: Human Healthmentioning
confidence: 99%
“…Radionuclides have also been reported and associated with dumpsites and landfills in Lagos State [93][94][95] [106]. These dangerous natural and artificial radiation materials from unregulated and unmanaged dumpsites and landfills released into inland water sources pose risks to resident organisms and population of humans, dependent directly on water for domestic purpose and consumption of resident aquatic organisms.…”
Section: Municipal Solid Waste and Inland Water Bodies In Nigeriamentioning
confidence: 99%
“…These results are below the (ICRP) maximum permitted limit and, therefore, have no significant radiological health effect on the people and the environment. Ref [25] investigated the activity concentrations of 40 K, 226 Ra, and 232 Th in an elevated radiation area of Oyo south-west Nigeria. In order to estimate the radiation dose acquire by the people, In situ gamma dose rates were likewise analyzed at each collection point.…”
Section: Natural Radioactive Deposit In Nigeriamentioning
confidence: 99%